Self-optimization of dense wireless sensor networks based on simulated annealing - Pinto, A. R. [UNESP]; Cansian, Adriano [UNESP]; MacHado, José Marcio [UNESP]; Montez, Carlos (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Wireless sensor network (WSN) Is a technology that can be used to monitor and actuate on environments in a non-intrusive way. The main difference from WSN and traditional sensor networks is the low dependability of WSN nodes. In this way, WSN solutions are based on a huge number of cheap tiny nodes that can present faults in hardware, software and wireless communication. The deployment of hundreds of nodes can overcome the low dependability of individual nodes, however this strategy introduces a lot of challenges regarding network management, real-time requirements and self-optimization. In this paper we present a simulated annealing approach that self-optimize large scale WSN. Simulation results indicate that our approach can achieve self-optimization characteristics in a dynamic WSN. © 2012 IEEE.
Keywords: Self-Optimization; Simulated Annealing; Wireless Sensor Networks; Non-intrusive; Real time requirement; Self-optimization; Wireless communications; Network management; Simulated annealing; Wireless sensor networks; Wireless telecommunication systems; Sensor nodes